Status and prospects of farm mechanization in Madhya Pradesh - Saha, K P; Singh, V V; Chaudhari, D (Journal of Agricultural Engineering, 2004)
This paper aims to study the status of mechanized farming practices adopted by the farmers for different farm operations of major cropping systems in the state of Madhya Pradesh with the purpose of identifying the existing mechanization gaps for different farm operations and to suggest the possible remedies to bridge those gaps. A total of 360 farmers were selected for collecting information by adopting multiple stratified random sampling technique. It was found that certain operations like weeding and plant protection were carried out by manually operated, low capacity equipment resulting into yield loss due to delay in conducting these farm operations. All of the farm operations except tillage were not completed within the available critical time. This was either due to inadequate use of mechanical power sources and high capacity implements, such as in the case of tillage, sowing, harvesting and threshing operations or due to not using mechanical power such as in the case of weeding and plant protection operations. Improvement of certain existing machines such as bullock or tractor drawn planters, bullock drawn seed cum fertilizer drill for small seeds, rice transplanters and bullock operated potato digger already developed in various research organizations, and development of new machines like self propelled power weeder, spraying attachment to power weeder and small combine harvesters are required to meet the mechanization requirement as expressed by the farmers.